Pemanfaatan Tanaman Maja (Aegle marmelos (L.) Correa) Sebagai Upaya Meningkatkan Stamina Pada Masa Pandemi Covid-19 Di Desa Mulyoagung, Dau, Malang - Sukian Wilujeng; Sonny Kristianto; Pramita Laksitarahmi Isrianto (LPPM Universitas Flores, 2022)
The Covid-19 pandemic has caused people to be more aware of the importance of maintaining health, in their lifestyle they prefer to return to nature. The purpose of this Penmas is to increase the body's immune/stamina to avoid disease attacks, including Covid-19. The method used is lecture, question and answer, and demonstration. What is discussed in this Public Education introduces maja fruit (Aegle marmelos (L) Correa) in terms of morphology, chemical content, potential, types of biotechnology, techniques in biotechnology, fermentation, benefits for health and packaging methods recommended by the Department of Health. . The conclusion: increase participants' knowledge about the importance of knowing more deeply about the existence of maja fruit (Aegle marmelos(L)Correa).Participants know how to make hygienic health drinks made from maja fruit (Aegle marmelos(L)Correa). Increase participants' knowledge of how to packaging processed beverages using plastic bottle packaging. The next stage plan will be training activities on how to cultivate and produce various processed food products made from maja fruit (Aegle marmelos(L) Correa), by presenting resource persons from the Agriculture Service and from the Trade Office to hold guidance for new entrepreneurs in the field of healthy food products.